An Effective and Easy-to-Implement Boundary Condition for Molecular Dynamics Simulations (Communications in Computational Physics, 2019)
This paper presents an absorbing boundary condition for molecular dynamics simulations of materials defects. The purpose of the boundary condition is to eliminates spurious reflections of phonons at the boundary and minimize the finite sizeeffect. In contrast to other existing methods, our emphasis is placed on the ease of implementation. In particular, we propose a method for which the implementation canbe done within existing molecular dynamics code, and it is insensitive to lattice structure, the geometry and space dimension of the computational domain. To demonstratethe effectiveness, the results from two test problems are presented.
Keywords: Molecular dynamics; boundary conditions; dislocation; crack; Krylov space.